Gestational hypertensive disease and small for gestational age infants in twin pregnancy: A systematic review and meta‐analysis. Issue 11 (16th August 2022) - Wang, Mingbo; Wang, Xin; Chen, Zhifang; Zhang, Feng
Abstract: Aim: The review is to explore the connection between gestational hypertension diseases (GHD) and small for gestational age (SGA) in twin pregnancies. Methods: According to the recommendations of PRISMA, relevant studies were systematically searched through PubMed, Web of Science, Cochrane Library, Embase from inception until January 16, 2022. Subgroup analysis was performed according to chorionicity and diagnostic criteria of SGA. Odds ratios (OR) were assessed to judge the link between GHD and SGA in twin pregnant women. A random‐effect model was used to estimate the pooled hazard ratio when there was significant heterogeneity ( I 2 > 50%); otherwise, a fixed‐effect model was conducted. Results: Seven articles containing 470 589 twin pregnant women were included. The increased risk of SGA was connected to the twin pregnancies complicated with GHD (OR = 1.57, 95% confidence interval [CI] = 1.10–2.24, p = 0.01). After subgroup analysis, the connection between SGA and GHD had no statistical significance (OR = 1.17, 95% CI = 0.95–1.44, p = 0.14) when the enrolled studies using the SGA diagnosis referred to singleton birth weight, but significant (OR = 2.14, 95% CI = 1.77–2.60, p <0.001) in the group using the SGA diagnosis referred to twin birth weight. Stratified by chorionicity, SGA was relevant to GHD in the dichorionic (DC) group (OR = 1.68, 95% CI = 1.17–2.42, p = 0.005), while not in the monochorionic (MC) group (OR = 1.68, 95% CI = 0.93–3.03, p = 0.09). More future articles are warranted to confirm these outcomes. Conclusions: Our review demonstrated that GHD in DC twin pregnancies was related to an enlarged risk of SGA. Two SGA diagnosis references led to different results. Twin pregnancies complicated with GHD were at significantly higher risk of SGA when twin birth weight reference was used.